1994
DOI: 10.1152/ajpheart.1994.266.1.h212
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial exclusion of IgG in rat tissues estimated by continuous infusion

Abstract: Interstitial exclusion, defined as the fraction of interstitial fluid volume inaccessible to a solute, was evaluated for immunoglobulin G (IgG) in selected tissues of rats by a method previously applied to serum albumin (29). IgG distribution volumes were also measured for intestine. 125I-labeled rat IgG was infused for 5 or 7 days (n = 4 rats each) with an implanted osmotic pump (Alzet). At the termination of infusion, the rat was anesthetized, nephrectomized, and injected with 51Cr-labeled EDTA (4 h) to labe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
34
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 0 publications
9
34
0
Order By: Relevance
“…Our observation that such treatment did not improve the transport of antibody correlates with the finding that the space available to IgG in these tumors is quite large compared with normal muscle (11). The interstitial space available to IgG is thus unlikely to be the limiting factor for antibody transport so a further increase in this space after hyaluronidase treatment does not result in an enhancement of antibody transport.…”
Section: Discussionsupporting
confidence: 78%
“…Our observation that such treatment did not improve the transport of antibody correlates with the finding that the space available to IgG in these tumors is quite large compared with normal muscle (11). The interstitial space available to IgG is thus unlikely to be the limiting factor for antibody transport so a further increase in this space after hyaluronidase treatment does not result in an enhancement of antibody transport.…”
Section: Discussionsupporting
confidence: 78%
“…This study showed that the corrected tissue concentration in muscle and skin exceeds that of plasma after 72 h for both ABD-(Z HER2:342 ) 2 and RSA, equal to the time to reach steady state using continuous infusion of RSA (72 h) (51). This is faster than what has been determined with infusion of IgG (120 h) (52). Thus, if IgG and ABD-(Z HER2:342 ) 2 were labeled with the same isotope, ABD-(Z HER2:342 ) 2 would reach steady state earlier, suggesting a more rapid accumulation of radioactivity in tissues and metastases.…”
Section: Discussionmentioning
confidence: 60%
“…Hyaluronan molecules are highly negatively charged, imbibe large amounts of water, and restrict the passage of negatively charged proteins (36). The proteins are restricted to Ïł50% of interstitial space (111,112). This means, for example, that in muscle interstitial space, which is 12-20% of the total tissue space, only 6 -10% of that space will be for transport of largemolecular-mass proteins.…”
Section: Interstitial Matrixmentioning
confidence: 99%